Factors related to exercise performance according to Theory of Planned Behavior in female students of Shahid Beheshti University of Medical Sciences - Hosseini, M; Khavari, Z; Yaghmaei, F; Alavi Majd, H (Advances in Nursing & Midwifery, 2010)
Back ground and aim The regular physical activity can lead to physical, psychological and social health. Studies have shown that %80 of Iranian people does not exercise. Therefore, due to the importance of exercise performance and concepts of Theory of Planned Behavior, different studies are needed regarding its related factors according to a theoretical framework. The aim of this descriptive correlational study was to determine factors related to exercise performance according to the Theory of Planned Behavior in female students in 2009. Materials and methods 444 female students were selected by stratified sampling method. Data collection tool was a questionnaire including 6 parts: 1- external variables, 2-attitiude to exercise, 3-subjective norms of exercise, 4- perceived control behavior toward exercise, 5- intention to exercise, and 6- exercise. Content validity index, face validity and reliability of the tool were identified by internal consistency and test-retest methods respectively. Data were analyzed by SPSS (ver. 15). Mean, standard deviation, distribution of frequency, regression and path analysis were calculated in data analysis. Findings Attitude and control of perceived behavior were positively correlated with intention to exercise and subjective norms, controlled perceived behavior regarding exercise as well as intention to exercise were positively correlated with exercise performance. Furthermore, control of perceived behavior was indirectly correlated with exercise performance through intention to exercise while subjective norms had no correlation with exercise performance. Conclusion Providing positive attitude and increasing the control of perceived behavior regarding exercise can motivate people to do it. Keywords: Exercise, Theory of Planned Behavior, Students. *Corresponding Author: Hosseini, Meimanat.Lecturer, Dept. of Community Health Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. E-mail: meimanathosseini@yahoo.com